The sandals of Pliny the Elder - Stadler, Thiago David (Romanitas - Revista de Estudos Grecolatinos, 2018)
In this article, I aim to introduce some features that compose a brief biography of Pliny the Elder. Supported by the testimonies of Pliny the Younger, I build two images that are sustained only when comprehended together: Pliny with sandals and Pliny without sandals. In the first case, there is the sharp explorer, the citzen that acts. In the second case, there is the studious, the scholar who meditates. It is in the contact of these two images that I present an experiment of how to build a more appropriate figure of Pliny the Elder. A fugitive figure at every new assert, but that reveals important aspects of a tipical Roman citzen of the I century.
Keywords: Biography; Roman Empire; Pliny the Elder